CAUSALITY ANALYSIS BETWEEN FINANCIAL PERFORMANCE AND HUMAN DEVELOPMENT INDEX: A CASE STUDY OF PROVINCES IN EASTERN INDONESIA - Sofia Arie Damayanty, Singgih Riphat, Hadi Setiawan, (Badan kebijakan Fiskal, 2016)
This research aims to examine the causal relationship between the provincial financial performance and the Human Development Index (HDI). The results of this research are important since it can be used as a guidance to make a sound policy of local government’s revenue and budget allocation which can improve the welfare or quality of the society. The methodology of this paper is a quantitative approach by using the Granger causality test. Several provinces in Eastern Indonesia are used as the object of research since those areas are underdeveloped compared to western Indonesia. Several financial ratios are used as the proxies of local financial performance. The results show that most of the financial performances do not have a causal relationship with HDI, except for several proxies in some provinces.